2003
DOI: 10.1046/j.1461-0248.2003.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers reduce egg provisioning with age

Abstract: Precise and comprehensive data on resource allocation into individual eggs are rare and this empirical void in the literature of life history strategies contrasts with the large number of theoretical studies. We show a marked decrease in reproductive investment in eggs with mother's age for egg size, sugar, protein, lipid and energy contents of eggs for a parasitic wasp. Egg size is a good predictor of offspring fitness, measured as survival of starving neonate larvae, but does not reveal possible biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
133
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 31 publications
8
133
1
Order By: Relevance
“…It was suggested in each study that the observed decreases in egg size were due to reduction in adult size resulting from limited feeding after the onset of reproduction, or the detrimental effects of aging. Similar decreases in propagule size with age have been reported for shortlived terrestrial species including the housefly (McIntyre & Gooding 2000), a parasitic wasp (Giron & Casas 2003), some butterflies (Fischer et al 2003), and 8 weedy herbaceous plants (Cavers & Steel 1984). Egg size has occasionally been reported to increase with age in arthropods (e.g.…”
Section: Introductionsupporting
confidence: 64%
“…It was suggested in each study that the observed decreases in egg size were due to reduction in adult size resulting from limited feeding after the onset of reproduction, or the detrimental effects of aging. Similar decreases in propagule size with age have been reported for shortlived terrestrial species including the housefly (McIntyre & Gooding 2000), a parasitic wasp (Giron & Casas 2003), some butterflies (Fischer et al 2003), and 8 weedy herbaceous plants (Cavers & Steel 1984). Egg size has occasionally been reported to increase with age in arthropods (e.g.…”
Section: Introductionsupporting
confidence: 64%
“…Within this experiment E. inaron did not experience sperm limitation per se, because spermatheca dissection confirmed the presence of ample sperm in virtually all mated individuals. However, sperm quality may have diminished with age (Ridley, 1988), or it is possible that female eggs receive greater nutrient provisioning than male eggs, and that older (lower quality) mothers opt to lay less costly male eggs (Giron and Casas, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, female-age dependent reduction in egg weight should result from a depletion in the nitrogen resources rather than in hydrocarbons (the former are not replenished by adult feeding: Wheeler, 1996; Boggs, 1997Boggs, , 2003O'Brien et al, 2002O'Brien et al, , 2004. Thus in butterflies, the size of the eggs should decrease as one of the two nutrients becomes scarce, rather than show a shift in the C : N ratio (as reported for parasitic wasps: Rivero et al, 2001;Giron & Casas, 2003;cf. Fischer et al, 2004, andO'Brien et al, 2004 for butterflies).…”
Section: Discussionmentioning
confidence: 92%